Pengaruh Transformasi Digital dan Kompetensi Pegawai Terhdap Kinerja Pegawai pada KPP Pratama Jombang - Muhammad Abrar Nurmansyah; Fandi Fatoni (Indo Publishing, 2026)
This study aims to test and analyze the influence of digital transformation and employee competency on the performance of KPP Pratama Jombang employees. This study is a quantitative research type. The sampling technique used saturated sampling with a sample of 78 respondents. Statistical analysis in this study used SEM (Structural Equation Modeling) with SmartPLS 4.0.9.9 software. The results of this study indicate that digital transformation has a positive and significant effect on employee performance. Employee competency has a positive and significant effect on employee performance. Digital transformation and employee competency have a positive and significant effect on employee performance. The implementation of digital transformation supported by adequate employee competency together can improve the performance of KPP Pratama Jombang employees, so that they can achieve work goals more effectively and efficiently.